Understanding Health Care Access Disparities Among Human Trafficking Survivors: Profiles of Health Care Experiences, Access, and Engagement - Price, Kathleen (Journal of interpersonal violence, 2021)
Human trafficking is associated with a profound burden of physical and psychological trauma. Survivors of trafficking interact with the health care system during and after their experiences of trafficking. Socioeconomic isolation, stigma, shame, guilt, fear of judgment, fear of retribution by traffickers, fear of law enforcement authorities, and other factors known to inhibit disclosure can exert a formative influence on survivors’ health care experiences, health care access, and health services engagement. Using a mixed qualitative-quantitative social science research method, known as by-person factor analysis (or Q-methodology), the current analysis systematically examines the scope of trafficking survivors’ health care experiences and perceptions of medical care, health care access behaviors, and degree of engagement with health services. Among 33 survivors of human trafficking surveyed, 21 met inclusion criteria for this analysis. Three distinct profiles of survivor health care experiences and health services engagement—Avoidant, Distrustful, and Constrained—are identified from the aggregate of survivors’ perceptions of medical care. Although there are salient differences across the three survivor profiles, a feeling of disenfranchisement is a common thread and directly related to health care access behaviors and health services engagement. Understanding that the feeling of disenfranchisement functions as a filter through which trafficking survivors perceive and experience medical care can help health care professionals take appropriate countermeasures. Implications for improving health care access and engagement include the implementation of trauma-responsive, culturally sensitive, and survivor-centered care practices.